Personality Traits and Work Values as Predictors of Vocational Interests Among University Students - Anna VERES; Tünde PÓKA (Studia Universitatis Babes-Bolyai, 2024)
Many organizations and career guidance professionals are curious about what personality traits can tell them about a person's potential, qualities and attitude to work. This study assessed the personality traits, work values and vocational interests of university students. The relationships between these three constructs were investigates, and more specifically, the extent to which personality traits and work value can predict vocational interest. Vocational interest determines one's career development and work choice. The study included 304 participants with a mean age of 25.4 years (SD=8.11). In our analysis, we used the HEXACO personality questionnaire, the Work Value Questionnaire measuring 15 subcategories and the RIASEC Vocational Interest Questionnaire. The aim of this study is to get a clearer picture of the relationship between personality traits, work values and vocational interests. The results show that personality traits are also predictive, but together with work value, they are stronger predictors of vocational interest. The results are presented in the light of career development.